1987
DOI: 10.1104/pp.84.3.609
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis of Euglena gracilis under Cobalamin-Sufficient and -Limited Growing Conditions

Abstract: Subeeilular Fractionation and Pumification of Chloroplasts. Partial trypsin digestion ofthe pellicle followed by mild mechanical disruption of Euglena ceUs and subcellular frationation by differential centifugation were conducted according to Shigeoka et al. (19).A suspension of chloroplasts was layered on the top of continuous Percoll (Lot No. 4634) gradients and centrifuged in a swingout rotor (Hitachi Reactions of Photosynthesis. Photosynthesis resulted in net 02 evolution from cells, which were cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Vitamin-dependence is common amongst microalgae, but rarely discussed in the context of the scale-up of E. gracilis cultivation (Croft et al, 2006). Euglena gracilis shows an absolute requirement for vitamins B 1 (thiamine) and B 12 (cobalamin), so complex E. gracilis media usually contain at least 50 ng/L and 10 ng/L, respectively, of these compounds (Isegawa et al, 1987; Shigeoka et al, 1987; Croft et al, 2005; Hasan et al, 2017). Accordingly, the supplementation of both vitamins, produced either by chemical synthesis (thiamine) or extracted from bacterial sources (cobalamin), would be a factor in a scaled-up E. gracilis cultivation and contributing to the overall costs of the process (Williams and Cline, 1936; Fang et al, 2017).…”
Section: Large-scale Cultivation Of E Gracilismentioning
confidence: 99%
“…Vitamin-dependence is common amongst microalgae, but rarely discussed in the context of the scale-up of E. gracilis cultivation (Croft et al, 2006). Euglena gracilis shows an absolute requirement for vitamins B 1 (thiamine) and B 12 (cobalamin), so complex E. gracilis media usually contain at least 50 ng/L and 10 ng/L, respectively, of these compounds (Isegawa et al, 1987; Shigeoka et al, 1987; Croft et al, 2005; Hasan et al, 2017). Accordingly, the supplementation of both vitamins, produced either by chemical synthesis (thiamine) or extracted from bacterial sources (cobalamin), would be a factor in a scaled-up E. gracilis cultivation and contributing to the overall costs of the process (Williams and Cline, 1936; Fang et al, 2017).…”
Section: Large-scale Cultivation Of E Gracilismentioning
confidence: 99%
“…CN-B12 reductase, which catalyzes the conversion of CN-B12 to OH-B12, has been detected in Euglena (Watanabe et al 1988d) whereas the other enzymatic systems involved in the synthesis of AdoB12 and MeB12 have not yet been characterized in mitochondria. Although no information is currently available on the chloroplastic system for co-enzyme B12 synthesis, Isegawa et al (1987) reported that MeB12 functioned as a coenzyme of methionine synthase in chloroplasts and photosynthetic activity was decreased during B12 deficiency due to the loss of photosystem I.…”
Section: Vitamin B12mentioning
confidence: 97%
“…P. tenera required B 12 and took up and acquired exogenous B 12 , but it is unclear whether the growth of all Porphyra species shows B 12 dependency. Although various B 12 -requiring microalgae contained B 12 -dependent methionine synthase and methylmalonyl-CoA mutase, , the occurrence and characterization of both B 12 -dependent enzymes have not been reported in Porphyra sp.…”
Section: General Nutrients Of Porphyra Sp (Nori) Productsmentioning
confidence: 99%
“…23 P. tenera required B 12 23 and took up and acquired exogenous B 12 , 24 but it is unclear whether the growth of all Porphyra species shows B 12 dependency. Although various B 12 -requiring microalgae contained B 12 -dependent methionine synthase and methylmalonyl-CoA mutase, 25,26 the occurrence and characterization of both B 12 -dependent enzymes have not been reported in Porphyra sp. Using liquid chromatography−electrospray ionization tandem mass spectrometry analysis, two corrinoids (major, B 12 ; minor, pseudovitamin B 12 ) (Figure 2B) were also detected in Chinese dried nori (unpublished data).…”
Section: ■ Introductionmentioning
confidence: 99%